Education Care Community as Solution for Education Inequality in West Sumatera within Post-Covid Times - Nindya Raihan Zani; Selvia Rahayu (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2022)
Acquiring an education is one of the Human Rights manifestations. Through education, someone can develop themselves to live a better life. Nowadays, the development of education in Indonesia is unequally distributed. The circumstances where students in urban are easier to access education than students in rural who have difficulty accessing education still exist. Furthermore, education inequality is exacerbated by the COVID-19 pandemic that changed the education system towards e-learning. It required students to quickly adapt to these conditions, although they are not ready to deal with them. West Sumatra is one of the provinces in Indonesia that has been implemented e-learning due to the COVID-19 pandemic. It causes educational inequality. Indirectly, the COVID-19 pandemic has divided students into several social classes due to their ability to access e-learning. Even though, education is a fundamental right for all human beings. This research dissected West Sumatra as the object of research. This aims to determine the extent of educational inequality that occurred in West Sumatra due to the COVID-19 pandemic. This research was uncovered by the concept of Marxism to articulate the educational inequality in West Sumatra during the COVID-19 pandemic. This research provides solutions based on the concept of capacity building, namely the establishment of The Education Care Community as a facilitator for students along West Sumatra to access education easily in the post-COVID times. This is done to realize equality of education for all students.